Controllable supramolecular assembly and architecture transformation by the combination of orthogonal self-assembly and competitive self-sorting assembly. Issue 48 (26th November 2019) - Yang, Ying; Li, Hui; Chen, Jiangmin; Xu, Fenfen; Duan, Zhaozhao; Liang, Tongxiang; Liu, Yang; Tian, Wei
Abstract : New supramolecular polymers were prepared by the combination of orthogonal self-assembly and competitive self-sorting assembly methods. Abstract : New linear supramolecular polymers SP1 and SP2 were prepared by the combination of orthogonal self-assembly and competitive self-sorting assembly methods. The photoluminescence of SP1- and SP2-based films can be decreased and enhanced, respectively, by adding basic ions.